Costs of food and meal leftover from modified meal program in the Sanglah Hospital - Ida Ayu Nyoman Triwini (Berita Kedokteran Masyarakat, 2021)
Objective: This study describes the cost of meals and the cost of leftovers from the modified feeding program at RSUP Sanglah Denpasar. Methods: This cross-sectional study is based on 76 adult inpatients who received modified meals using the non-randomized purposive sampling technique in three months in RSUP Sanglah Denpasar. Statistical analysis used statistical version 14 with the Shapiro Wilk data normality test, non-parametric tests, namely the chi-square test and the Spearman rank correlation test. Results: The average cost of modified food is IDR 93.917, while the standard price of hospital meals is IDR 47.564. The average amount of food leftovers was 27,94%, with the cost of missing from food scraps of IDR 9.637, while the standard of leftovers was ≤20%, and the cost of leftovers was IDR 9,513. Food and leftovers' cost has a significant relationship with the value of p 0.000 (p <0.05), has a positive correlation, and has a strong relationship with a value of r (+) 0.4944 (r> 0.40). If the cost of food increases, the cost of leftovers will increase as well. Conclusions: The modified feeding program at RSUP Sanglah Denpasar is less effective. Leftovers' cost is greater than the hospital's standard costs.Tujuan: Penelitian ini dilakukan untuk mengetahui gambaran biaya makan dan biaya sisa makanan dari program pemberian makanan modifikasi di RSUP Sanglah Denpasar. Metode: Penelitian ini menggunakan rancangan observasional dengan desain cross sectional dilakukan selama 3 bulan di RSUP Sanglah Denpasar. Subjek penelitian adalah 76 pasien dewasa rawat inap mendapatkan makanan modifikasi dengan teknik nonrandomized purposive sampling. Analisis statistik menggunakan stata versi 14 dengan uji normalitas data shapiro wilk, uji non parametrik, yaitu uji chi-square dan uji korelasi spearman rank. Hasil: Biaya makanan modifikasi rerata sebesar Rp93.917,- sedangkan standar biaya makan rumah sakit sebesar Rp47.564,-. Jumlah sisa makanan modifikasi rerata sebesar 27,94% dengan biaya yang hilang dari sisa makanan modifikasi sebesar Rp9.637,- sedangkan standar sisa makanan ≤20% dengan biaya sisa makanan sebesar Rp9.513,-. Biaya makan dengan biaya sisa makanan modifikasi memiliki hubungan yang signifikan dengan nilai p 0,000 (p<0,05), sifat korelasi positif dan memiliki keeratan kuat dengan nilai r(+)0,4944 (r>0,40) artinya jika biaya makan mengalami kenaikan maka biaya sisa makanan juga akan mengalami kenaikan. Simpulan: Program pemberian makanan modifikasi di RSUP Sanglah Denpasar berjalan kurang efektif dan efisien, terlihat dari nilai biaya makan dan biaya sisa makanan modifikasi lebih besar dibandingkan standar biaya yang ditetapkan rumah sakit.